Photophysical transformations induced by chemical substitution to salicylaldimines. Issue 12 (12th March 2020) - Barboza, Cristina A.; Gawrys, Pawel; Banasiewicz, Marzena; Suwinska, Kinga; Sobolewski, Andrzej L.
Abstract : The role of electron-acceptor strength and microenvironment polarity on the photophysical properties of salicylaldimines. Abstract : A series of different electron-deficient aromatic substituents were used to investigate the role of the electron-acceptor strength on the photophysical properties of salicylaldimine derivatives. These molecules were synthesised and characterised through X-ray diffraction, absorption and emission spectroscopies. Their photochemical reaction mechanisms and properties were explored with the aid of ab initio methods of quantum chemistry. Our results allow us to clarify the dependence of the multiple emission bands on the polarity of the solvent and on the substitution of electron donating and accepting groups to the salicylaldimine core.